Does 'Telecentre' Mean the Centre is Far Away? Telecentre Development in South Africa - Benjamin, Peter (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2000)
This article questions the role of telecentres as a vehicle for development in developing countries, particularly in South Africa. The organisation of the emerging Information Age is, in the words of Manuel Castells, 'Global Informational Capitalism'. There are forces that increase the power of a global elite while large numbers of people are excluded. This 'digital divide' puts at further disadvantage many people in poor areas in rich Northern countries and a majority of people living in African countries. The imagery that surrounds the new Information and Communications Technology speaks of unlimited potential that can bring great benefit to development problems. Historical examples of the telegraph system and the introduction of railways into Africa are cited to show the difference between rhetoric and reality. In the last few years, there has been great enthusiasm for telecentres as a vehicle for providing access to telecommunications and other information technologies in developing countries. The projects in South Africa and other countries are outlined. The various possible aims for telecentres are next discussed, concluding that actually they are a weak tool for addressing universal access to telephony, though there are many other objectives they can have. Greater clarity is required in deciding what telecentres projects are aiming to do. If these issues are not thought through, there is a risk that telecentres will either 'fail' and waste money, or will serve to bring the division between the 'information haves' and 'have-nots' into communities - creating a local digital divide. Similarly, more thought must be given to how to move beyond a number of pilot projects (many faltering) towards ways of providing genuine universal access.